Cytomorphological Analysis of Neoplastic Lesions of Neck Node with Special Reference to Lymphomas - Devi, Junu (Annals of Pathology and Laboratory Medicine, 2020)
BACKGROUND: Neoplastic lesions of lymph node in cervical region pose a diagnostic delima and very often cytological diagnosis proves invaluable. An early diagnosis of the lesions is essential for proper management. To assess the frequency distribution and cytological analysis of various neoplastic lesions of lymph node with special reference to the lymphoma. MATERIAL AND METHODS: this is a cross-sectional study which provides analysis of 164 neoplastic lesions of lymph node out of 758 lymph node aspirate. Cytomorphological pattern and cellular detail are reviewed carefully and diagnosis were made. Histopathological and immunohistochemical correlation done wherever needed. RESULTS: Out of 164 neoplasms 86.59% secondary neoplasms(61.27% SCC, 19.72% Adenocarcinoma,15.49% poorly differentiated carcinoma,0.70% undifferentiated carcinoma, 0.70% mucoepidermoid carcinoma, 0.70% papillary thyroid carcinoma,1.41% leukemic deposit),12.2% lymphoid neoplasms. M:F = 1.2:1. Diagnostic accuracy was calculated as 98.67%, and false positive rate 1.3% CONCLUSION: fine needle aspiration cytology is invaluable in rapid diagnosis of lymph node neoplasms of cervical region however histological confirmation and immunohistochemical analysis is mandatory in certain tumors specially lymphomas, poorly and undifferentiated carcinoma for accurate diagnosis and proper management.